Astrocyte-derived extracellular vesicles enhance the survival and electrophysiological function of human cortical neurons in vitro. (April 2021) - Chun, Changho; Smith, Alec S.T.; Kim, Hyejin; Kamenz, Dana S.; Lee, Jung Hyun; Lee, Jong Bum; Mack, David L.; Bothwell, Mark; Clelland, Claire D.; Kim, Deok-Ho
Abstract: Neurons derived from human induced pluripotent stem cells (hiPSCs) are powerful tools for modeling neural pathophysiology and preclinical efficacy/toxicity screening of novel therapeutic compounds. However, human neurons cultured in vitro typically do not fully recapitulate the physiology of the human nervous system, especially in terms of exhibiting morphological maturation, longevity, and electrochemical signaling ability comparable to that of adult human neurons. In this study, we investigated the potential for astrocyte-derived extracellular vesicles (EVs) to modulate survival and electrophysiological function of human neurons in vitro . Specifically, we demonstrate that EVs obtained from human astrocytes promote enhanced single cell electrophysiological function and anti-apoptotic behavior in a homogeneous population of human iPSC-derived cortical neurons. Furthermore, EV-proteomic analysis was performed to identify cargo proteins with the potential to promote the physiological enhancement observed. EV cargos were found to include neuroprotective proteins such as heat shock proteins, alpha-synuclein, and lipoprotein receptor-related protein 1 (LRP1), as well as apolipoprotein E (APOE), which negatively regulates neuronal apoptosis, and a peroxidasin homolog that supports neuronal oxidative stress management. Proteins that positively regulate neuronal excitability and synaptic development were also detected, such as potassium channel tetramerization domain containing 12 (KCTD12), glucose-6- phosphate dehydrogenase (G6PD), kinesin family member 5B (KIF5B), spectrin-alpha non-erythrocytic1 (SPTAN1). The remarkable improvements in electrophysiological function and evident inhibition of apoptotic signaling in cultured neurons exposed to these cargos may hold significance for improving preclinical in vitro screening modalities . In addition, our collected data highlight the potential for EV-based therapeutics as a potential class of future clinical treatment for tackling inveterate central and peripheral neuropathies.